Fabrication and Characterization of a Modified Conjugated Molecule-Based Moderate-Temperature Curing Epoxy Resin System - Ding, Liu; Yang, Ji Ping; Hao, Xiao Li; Tong, Ting (Frontiers in Materials, 2020)
2-methylimidazole derivative (EGE-2MI) was synthesized through the reaction of ethyl glycidyl ether (EGE) with conjugated molecule 2-methylimidazole (2-MI). The structure was confirmed by Fourier transform infrared spectroscopy (FTIR)、1H-nuclear magnetic resonance spectroscopy (1H-NMR) and differential scanning calorimeter (DSC). The synthesized EGE-2MI was applied in epoxy resin E-51 as latent curing agent. Kinetics of the curing reaction were studied by DSC method, optimum curing process parameters were determined, storage life of the resin system at room temperature was evaluated, mechanical properties of the moderate-temperature cured products were also tested and analyzed. The results revealed that epoxy resin system using EGE-2MI as curing agent can be efficiently cured at 110 120 °C, with an activation energy of 86.34 kJ/mol. The storage period of EGE-2MI/ Cyanate resin (CE) system can reach 14 days under ambient temperature. In addition, the cured mixture with EGE-2MI/CE has a tensile strength of 40 MPa and an Al-Al adhesion shear strength of 20.11 MPa.